POETIC INTERPRETATION OF HIJRON IN NAVOI’S LYRICS - Durdona Zohidova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article given below is about the problem of artistic interpretation in Navoi’s lyrics of a lover’s dream of a meeting, which was sung by him with unsurpassed skill.